El derecho a la verdad bajo la Convención Internacional para la protección de todas las personas contra las desapariciones forzadas: significado y obligaciones del Estado - Banuelos Mejia, Tania (Revista Tribuna Internacional, 2024)
Truth as a right has been enshrined in treaty law for the first time under the International Convention for the Protection of All Persons from Enforced Disappearance (ICPPED). The right to the truth in this context has very specific objectives given the nature and elements of the crime of enforced disappearance. However, its meaning and the precise obligations that it creates for States parties are not well known, allowing a normative gap for States to elude its implementation and undermining efforts towards its realization. This article seeks to narrow that gap by analyzing both the ICPPED and the work of the Committee on Enforced Disappearances in interpreting the right. It finds that the right to the truth under the ICPPED is central for clarifying cases of enforced disappearance as it has the objective of establishing the fate and whereabouts of a disappeared person and triggers the State’s obligations to search and investigate. It concludes that the effective implementation of the right is also fundamental for combatting impunity for enforced disappearance, as it seeks to compel the State to end its denial of the truth.